2023
DOI: 10.3390/plants12071518
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the NAC Transcription Factor Family during Early Seed Development in Akebia trifoliata (Thunb.) Koidz

Abstract: This study aimed to gain an understanding of the possible function of NACs by examining their physicochemical properties, structure, chromosomal location, and expression. Being a family of plant-specific transcription factors, NAC (petunia no apical meristem and Arabidopsis thaliana ATAF1, ATAF2, and CUC2) is involved in plant growth and development. None of the NAC genes has been reported in Akebia trifoliata (Thunb.) Koidz (A. trifoliata). In this study, we identified 101 NAC proteins (AktNACs) in the A. tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Both the selection style and duplication type of members are the two most important factors when we investigate the evolutionary history of a given gene family. Here, we only found one homogenous gene pair (AktPG15 and AktPG17) with a Ka/Ks value (1.122) larger than 1 among a total of 467 homologous gene pairs, while all the others were less than 1 or even 0.5 (Supplementary Table S1), which suggested that AktPGs as well as AktNBSs [43], AktMADS-boxs [44], AktWRKYs [45], AktNACs [46], AktSODs [47], and AktDofs [48] experienced strong purifying selection in the evolutionary process.…”
Section: Putative Evolutionary Events Experienced By Aktpgsmentioning
confidence: 86%
“…Both the selection style and duplication type of members are the two most important factors when we investigate the evolutionary history of a given gene family. Here, we only found one homogenous gene pair (AktPG15 and AktPG17) with a Ka/Ks value (1.122) larger than 1 among a total of 467 homologous gene pairs, while all the others were less than 1 or even 0.5 (Supplementary Table S1), which suggested that AktPGs as well as AktNBSs [43], AktMADS-boxs [44], AktWRKYs [45], AktNACs [46], AktSODs [47], and AktDofs [48] experienced strong purifying selection in the evolutionary process.…”
Section: Putative Evolutionary Events Experienced By Aktpgsmentioning
confidence: 86%
“…The NAC transcription factor family is a plant-specific transcription factor family, which plays key roles in stress response and tolerance by regulating the expression of stress-related genes in plants [1,40]. Previous studies have demonstrated that NAC genes also have a great impact on plant cold tolerance and some key cold-related regulation pathways have been revealed, such as the NAC-DREB and NAC-CBF-COR signaling pathways [41].…”
Section: Discussionmentioning
confidence: 99%
“…The cis-acting element of the promoter region regulates the exact commencement of gene transcription and transcriptional efficiency by binding to transcription factors, it can determine the core area of transcriptional activation ( Wittkopp and Kalay, 2011 ; Ding et al., 2021 ; Liu et al., 2023 ; Rui et al., 2023 ). The NAC family has a substantial amount of cis-acting elements associated to light sensitivity, hormone response, biotic and abiotic stress response that are speculated to have a role in D. nobile growth and development, stress tolerance, and hormone signaling.…”
Section: Discussionmentioning
confidence: 99%
“…From the phylogenetic tree of NAC gene family in D. nobile, it can be seen that the D. nobile NAC gene family can be divided into 11 subfamilies and the family members are unevenly distributed in each subfamily. Combining the results of collinearity analysis and the phylogenetic tree of NAC gene family in D. nobile and Arabidopsis NAC gene family, it was discovered that there are eight pairings of genes with a high degree of similarity(DnoNAC27 The cis-acting element of the promoter region regulates the exact commencement of gene transcription and transcriptional efficiency by binding to transcription factors, it can determine the core area of transcriptional activation (Wittkopp and Kalay, 2011;Ding et al, 2021;Liu et al, 2023;Rui et al, 2023). The NAC family has a substantial amount of cis-acting elements associated to light sensitivity, hormone response, biotic and abiotic stress response that are speculated to have a role in D. nobile growth and development, stress tolerance, and hormone signaling.…”
Section: Discussionmentioning
confidence: 99%